OPTIMALISASI PELAYANAN PUBLIK MELALUI PENDEKATAN KOLABORATIF TRIPLE HELIX: SUATU IDENTIFIKASI DAN MENGATASI PATOLOGI PELAYANAN KEPENDUDUKAN DI DESA SUKOMAJU - Fahreza Nur Azizah; Sri Wilujeng; Hary Priyanto (Yayasan Nusantara Hasana Berdikari, 2025)
The existence of illegal levies in the delivery of public services greatly disrupts the success targets of government programs. The fact of illegal levies makes society hostage. One side wants to reject it but on the other side it needs the output of the service program. The government must routinely monitor and evaluate service program implementers. The government must serve the people, not the people serving the government. This research is to interpret and analyze pathology management in the implementation of population services using the collaborative triple helix principle. Researchers apply qualitative research methods according to constructive and participatory principles. Primary data was obtained from interviews, and secondary data was obtained from the results of literature studies and various regulations relevant to the substance of the research. The conclusion obtained is that the function of the Government is not only responsible for designing public service policies, but also must provide assurance that its apparatus has implemented it effectively, collaborated with interested parties, and ensured that policy implementation has a positive impact on society. As for the recommendations set out in this research, triple helix collaboration can form a comprehensive governance system and integrate various interrelated dimensions in building village government that is effective, transparent, fair, and able to face future challenges by maintaining integrity and accountability.